USING SONG QUIZZES THROUGH ESOL COURSE WEBSITE TO IMPROVE STUDENTS’ LISTENING SKILL AT ELEVENTH GRADE OF SMAN 18 MAKASSAR - Monica Sinai; Andi Hamzah Fansury; Rampeng Rampeng (Teaching English as a Foreign Language Overseas Journal, 2023)
The objective of the research was to know the use of song quizzes through ESOL Course website to improve students’? listening skill in a creatively learning methods. This research used experimental method. This research conducted in three steps namely as pre-test, treatment, and post-test. The population of this research was Class XI at the First Semester of SMAN 18 Makassar in 2022/2023 academic year and sample of this research is Class XI IPA 1 with number of students are 35 students. Data collected by using pre-test, treatment, and post-test. After conducted this research, the researcher concludes that using song quizzes through ESOL Course website improve students’? listening skill. It is proved by the mean score of the students in pre-test, treatment, and post-test. The mean score of the pre-test was 67.40, and the post-test students? score was 82.37. it shows that there is a different between students mean score in pre-test and post-test. Based on the analysis, it can be concluded that using song quizzes through ESOL Course website greatly influences to improve students’? listening skill at eleventh grade of SMAN 18 Makassar